Opisthorchiasis and cholangiocarcinoma in South East Asia: an unresolved problem - Hughes,T; O'Connor,T; Namwat,N; Loilome,W; Techasen,A; Crossey,MME; Khan,SA; Andrews,RH; Khuntikeo,N; Yongvanit,P; Sithithaworn,P; Taylor-Robinson,SD (International Journal of General Medicine, 2017)
The prevalence of cholangiocarcinoma (CCA) in Southeast Asia is much higher than other areas of the world. Eating raw, fermented or undercooked cyprinid fish, infected with the liver fluke, Opisthorchis viverrini sensu lato, results in chronic biliary inflammation, periductal fibrosis, and increased cancer risk. There may be associated glomerulonephritis. The process of infection is difficult to disrupt because eating practices have proven extremely difficult to change, and the life cycle of the fluke cannot be broken due to high prevalence in canine and feline reservoir hosts. Fecal analysis and ELISA tests can be used to diagnose opisthorchiasis. Diagnosis of CCA is complex, partly due to the lack of definitive imaging characteristics and also due to the difficulty of obtaining samples for cytology or histology. This cancer has proven to be resistant to common chemotherapy treatments and so the two avenues of treatment available are surgical resection and liver transplantation, both requiring early detection of the tumor for the best chances of success. Late presentation of symptoms reduces the chances of successful surgical intervention. While liver fluke infections can be treated with praziquantel, individuals will often become re-infected, and multiple reinfections can be more harmful than a singular, long term infection. A key research need is for the detection and characterization of novel biomarkers in all parts of the carcinogenic pathway for early diagnosis.